Indonesia-Australia Cooperation in Handling Environmental Issues through the IAFCP Program (Indonesia-Australia Forest Carbon Partnership) - Vivi Yunia Ifada; Badrus Sholeh (Universitas Airlangga, 2021)
Global environmental issue is a matter of concern and no longer underestimated,humans must strive to maintain environmental sustainability and safety,namely in regards to carbon emissions increase. REDD+ is a mechanism thatoffers reduced carbon emissions by focusing on reducing deforestation andforest degradation. Limited budget for the environment, pushes Indonesia forgepartnerships with Australia in 2008 through Australia on Indonesia-AustraliaForest Carbon Partnership (IAFCP). IAFCP is an example of a partnership thatsignificantly supports the achievement of GHG emission reductions in Indonesiaby reducing deforestation and improving sustainable forest management. Thisresearch focuses on Indonesia’s national interest to maintain the sustainabilityin the environmental sector by reducing emissions through the IAFCP. Theresearch method uses descriptive analysis, also Green Theory and bilateralcooperation concept. The purpose of this article is to find out the contribution ofIndonesia-Australia collaboration through the IAFCP program in the success ofovercoming environmental issues that occur in Indonesia.